2016
DOI: 10.17795/iji-35375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Genotypes of Staphylococcus aureus Strains Isolated From Healthcare Workers in Duhok City, Kurdistan Region, Iraq

Abstract: Background: Nasal carriage of Staphylococcus aureus and its virulence determinants are major risk factors for subsequent infections and transmission. Objectives: The current study aimed to determine the prevalence of panton-valentine leukocidin (PVL) gene, the SCCmec types, and the prevalent methicillin-resistant Staphylococcus aureus (MRSA) genotypes in strains isolated from healthcare workers (HCWs). Materials and Methods: DNA was extracted from 114 frozen S. aureus strains amongst them MRSA isolates were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
(16 reference statements)
3
15
3
Order By: Relevance
“…The prevalence of HBV and HCV has been studied previously in Iraq in different groups, such as blood donors, healthcare workers, and thalassaemia patients (5)(6)(7)(8). In a study conducted in Iraq on 7900 blood donors, it was found that 0.78% of donors were HBsAg positive, and only 0.013% of samples were HCV positive (9).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV and HCV has been studied previously in Iraq in different groups, such as blood donors, healthcare workers, and thalassaemia patients (5)(6)(7)(8). In a study conducted in Iraq on 7900 blood donors, it was found that 0.78% of donors were HBsAg positive, and only 0.013% of samples were HCV positive (9).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV varies from less than 1% in the developed world to more than 8% in some Asian countries (3)(4)(5). The prevalence of HBV has been studied in Iraq and it was found that HBsAg positivity was around 1% (6)(7)(8). Chronic HBV infection may predispose to liver cirrhosis, liver failure, and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV in Duhok was around 1% (2,3,10). Public healthcare providers have set an ambitious plan to eradicate HBV infection by 2030 (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HBV infection varies from one country to another ranging from less than 1% in Western countries to up to 10% in some Asian countries (1). In Iraq, the prevalence of HBV is around 1% (2,3). It is estimated that 400 million people are currently infected with the virus.…”
Section: Introductionmentioning
confidence: 99%